Use and non-use of humor in academic ESL classrooms. - Ziyaeemehr, Ali; Kumar, Vijay; Abdullah, Mohd Faiz (Canadian Center of Science and Education, 2011)
A substantial body of research emphasizes the importance of humor in teaching/learning processes; however, research on the reasons for non-use of humor in academic contexts has enjoyed scant attention. Addressing this gap, this study examines the reasons for instructors’ humor avoidance taking into account student perceived benefits of using humor in academic ESL classrooms. Data were collected through an open-response questionnaire. Participants in a university in Malaysia were asked to provide their views on: (a) the reasons some instructors avoid using humor, and (b) the benefits of using humor in L2 classes. Responses were grouped into relating categories and content analyzed. “Humor is not in their personality,” “they lack competence to create humor in L2,” and “they are more syllabus-oriented” were the most frequently cited reasons for the non-use of instructor humor. Perceived benefits of instructor humor were placed into three major categories: psychological, social and instructional. Implications of these findings are explored within the content of second language education.